Purple Yam (Dioscorea alata) Tuber Improves the Histological Appearance of the Ampulla of the Uterine Tube in a Mouse Model of Endometriosis - Sri Nabawiyati Nurul Makiyah; Sherly Usman; Rabiatul Adawiyah (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to examine the effect of Dioscorea alata ethanol extract (EEDA) on the histological features of the ampulla of the uterine tube in a mouse model of endometriosis. This was a true experimental study with a posttest-only control group design using 30 mice divided into six groups: a normal control group (K), a negative control group (KN) induced with endometriosis, a positive control group (KP) induced with endometriosis and treated with letrozole, and three treatment groups induced with endometriosis and administered EEDA at doses of 50, 250, and 500 mg/kg body weight. The observed parameters included inflammatory cell infiltration, epithelial damage, and fibrosis. Data were analyzed using the Kolmogorov–Smirnov test for normality, which showed that the data were not normally distributed; therefore, the nonparametric Kruskal–Wallis test followed by the Mann–Whitney post hoc test was applied. The results showed that the KN group had the highest scores for inflammatory cell infiltration, epithelial damage, and fibrosis (p < 0.05). Administration of EEDA significantly reduced all three parameters compared with the KN group (p < 0.05), with histological improvement increasing in a dose-dependent manner and the most optimal dose observed at 500 mg/kg body weight. It can be concluded that Dioscorea alata ethanol extract may improve the histological features of the ampulla of the uterine tube through anti-inflammatory and antifibrotic mechanisms at an optimal dose of 500 mg/kg body weight; however, the specific molecular mechanisms still require further verification. These findings indicate the potential of Dioscorea alata ethanol extract as a candidate herbal-based alternative therapy in an experimental model of endometriosis.